1) Plug in -2y + 5 for x in the second equation:
2(-2y + 5) + 6y = 16
2) Distribute:
-4y + 10 + 6y = 16
3) Combine like variables:
2y + 10 = 16
4) Isolate "y":
2y + 10 = 16
- 10 -10
2y = 6
y = 3
5) Plug "y" back into the first equation to find "x":
x = -2y + 5
x = -2(3) +5
x = -6 + 5
x = -1
6) Your answer is:
y = 3, x = -1
2006-12-02 12:21:58
·
answer #1
·
answered by pdate07 2
·
1⤊
2⤋
You have to substitute the x value into the second equation like this:
2(-2y+5)+6y=16 then distribute the 2
-4y+10+6y=16 then minus the 10 from both sides
-4y+6y=6 then comebine the -4y with the 6y
2y=6 then divide both sides by two and you get that
y=3 then substitute the y value in the first equation
x=-2(3)+5 then multiply the negative 2 and the 3
x=-6+5 then add the remaining numbers and u get
x=-1 so your final answers are x=-1 and y=3
2006-12-02 12:30:19
·
answer #2
·
answered by lilwhitekid41 2
·
0⤊
1⤋
First eqn. is rewritten as x+2y=5 or 2x+4y=10. Second eqn. is
2x+6y=16. Subtract first from the second to get 2y=6 which gives y=3. Hence x=-2*3+5=-1.
2006-12-02 13:31:37
·
answer #3
·
answered by greenhorn 7
·
0⤊
1⤋
Plug in the -2y+5 for x in the second equation. Your new equation will read: 2(-2y+5) + 6y=16. Distribute the 2 to each part in the parentheses so you get: -4y+10 + 6y = 16.
Then bring the y together and the numbers together on the other side of the equal sign so you have: 2y = 6.
Last, divide by 2on both sides to get: y=3
2006-12-02 12:21:02
·
answer #4
·
answered by Jenn F 2
·
0⤊
4⤋
plug in for x in 2x+6y=16 to 2(-2y+5)+6y= 16
= -4y + 10 + 6 y = 16
then add all common terms
= 2y = 6
then 2 divided by 6 = 3
y=3
then plug it in 2x+6*3=16
=2x+ 18 = 16
then do the same add all commmon terms
= 2x=-2
= x=-1
2006-12-02 12:27:04
·
answer #5
·
answered by azn boy 2
·
1⤊
1⤋
x=-2y+5
2x+6y=16
2(-2y+5)+6y=16
-4y+10+6y=16
2y=6
y=3
2x+6(3)=16
2x+18=16
2x=-2
x=-1
or you could start by multiplying the first equation by -3 and adding it to the second if you find that easier to understand
2006-12-02 12:22:13
·
answer #6
·
answered by Peter 3
·
1⤊
1⤋
x+2y=5
multiply by -2
-2x-4y=-10
2x+6y=16
adding
2y=6
dividing by 2
y=3
sub y=6 in (1)
x=-2(3)+5
=-6+5
=-1
solution set(-1,3)
2006-12-02 12:22:26
·
answer #7
·
answered by raj 7
·
1⤊
1⤋
2(-2y+5)+6y=16
-4y+10+6y=16
2y=6
y=3
x= -2(3)+5
x= -6+5
x= -1
2006-12-02 12:19:36
·
answer #8
·
answered by 7
·
1⤊
2⤋
substitute -2y+5 for x into the second equation. Get y. Then solve the first eq for x.
For systems SUBSTITUTE
2006-12-02 12:22:54
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋
x=-2y+5
-5 -5
x-5=-2y
/-2 /-2
y=-2x+2.5
2x+6y=16
-2x -2x
6y=-2x+16
/6 /6
y=1/3x+2.66
2006-12-02 12:27:52
·
answer #10
·
answered by Anonymous
·
0⤊
2⤋